Mixed logic systems. - Remedios, Rene Dos
This paper presents, in an introductory manner, a method of creating and documenting digital circuit schematic diagrams. The method emphasizes a technique of generating schematic diagrams which maximizes their semantic content. This is achieved through the use of "natural' logic operators and through a convention which relieves the designer from having to think about final implementation details while designing the circuit. This paper also aims to show the mixed logic is a viable alternative to the present methods of teaching digital electronics. Unfortunately, the method, though widely accepted in industry is not given its due prominence by the academe.